2021
DOI: 10.3389/fmicb.2021.657238
|View full text |Cite
|
Sign up to set email alerts
|

Salt Tolerance Mechanism of the Rhizosphere Bacterium JZ-GX1 and Its Effects on Tomato Seed Germination and Seedling Growth

Abstract: Salinity is one of the strongest abiotic factors in nature and has harmful effects on plants and microorganisms. In recent years, the degree of soil salinization has become an increasingly serious problem, and the use of plant growth-promoting rhizobacteria has become an option to improve the stress resistance of plants. In the present study, the salt tolerance mechanism of the rhizosphere bacterium Rahnella aquatilis JZ-GX1 was investigated through scanning electron microscopy observations and analysis of gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
(43 reference statements)
0
17
0
Order By: Relevance
“…This indicates that ZS-3 has an additional mechanism to limit plant Na + accumulation. The concentrations of intracellular and extracellular Na + were lower in Rahnella aquatilis JZ-GX1 inoculated with LB liquid medium (CK) under salt stress, indicating that the bacteria can consume Na + in the medium ( Li et al, 2021 ). ZS-3 is a salt-tolerant strain that tolerates 8% salt in LB, corresponding to moderate salt stress ( Lu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that ZS-3 has an additional mechanism to limit plant Na + accumulation. The concentrations of intracellular and extracellular Na + were lower in Rahnella aquatilis JZ-GX1 inoculated with LB liquid medium (CK) under salt stress, indicating that the bacteria can consume Na + in the medium ( Li et al, 2021 ). ZS-3 is a salt-tolerant strain that tolerates 8% salt in LB, corresponding to moderate salt stress ( Lu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rahnella aquatilis JZ-GX1 is a strain of plant-promoting bacteria that was isolated from the rhizosphere of Pinus massoniana in our previous study ( Li and Wu, 2014 ). A previous study showed that JZ-GX1 significantly increased the germination rate, germination potential, fresh weight, primary root length and stem length of tomato seeds under salt stress, and it is a moderately salinophilic bacterium with good growth-promoting function ( Li et al, 2021 ). However, it is not clear whether VOCs from this strain can promote plant growth under salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…The germination rates of seeds in media supplemented with different concentrations of colchicine were recorded every day, until the 21st day, when the seeds did not germinate anymore. Starting on the 2nd day of observation on culture tubes, the germinated seeds based on a radicle length of 0.2 cm were used as the germination standard (Li et al, 2021 ). The germination rate reached its highest values on the 4th day, and then the germination potential was calculated based on the number of germinated seeds by Day 4.…”
Section: Methodsmentioning
confidence: 99%